PEKERJA ANAK DI USIA SEKOLAH (Pada Masyarakat Petani Sawit Di Kelurahan Kempas Jaya KecamatanKempas Kabupaten Indragiri Hilir) - Kartika "; M. Razif " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The child is one of the nation's next generation, therefore they should be prepare and also can be directed at early stages so that they can grow and develop into healthy children of both physical and spiritual, so that in future they can be kids who advanced, self-sufficient and prosperous. Thus will realize the quality of resources in the future. Child workers in school-age children who were supposed to be attending but they work and it does not want to attend school again. Here children made economic factors that support the sustainability of the family to meet the needs of the family. The population in this research is a school-age child workers who do jobs as labourers Palm harvesters, local coconut harvesters, workers ' and domestic workers who numbered 11 children. Child workers in school age here belongs to underprivileged children who due to poverty, even though at the moment the Government has helped ease the cost of these things however geratis SPP have not been able to help the child. Kids here that do the work instead of keterpaksaan elements of plantation owners or those who require the labor of the children but the ability of the child to do chores in the Neighborhood Kempas Jaya Subdistrict of Kempas Regency Indragiri HilirKey word : Child, School age, Worker